Estudio descriptivo de la inteligencia artificial para el fortalecimiento de la creatividad e innovación en los estudiantes de décimo año de educación general básica, de la unidad educativa Santa Mariana de Jesús Martínez Barba, del cantón San José de Chimbo, provincia de Bolívar, durante el periodo lectivo 2023 - 2024 - Gluber Fabricio, Gaona Vivanco (2024)
The research report conducted in the Educational Unit "Santa Mariana de Jesús" Martínez Barba, in the Canton San José de Chimbo, Province of Bolivar, during the period 2023-2024, focused on analyzing the impact of artificial intelligence in the improvement of creativity and innovation in the students of Tenth Year of General Basic Education. This study arises from the imperative need to innovate in education, especially about the integration of artificial intelligence, through the implementation of various AI tools in pedagogy. The main objective was to assess the level of knowledge and understanding of students about AI, identifying their perceptions and prejudices, in order to develop a pedagogical guide aimed at enhancing creativity and innovation. A quantitative research approach based on the socio- critical paradigm, designed to analyze phenomena in specific contexts. Various data collection methods were employed, including participant observation, to obtain a comprehensive view of the subject under investigation. In conclusion, artificial intelligence appears as a tool capable of stimulating creativity in students; its effective use allows teachers to implement new techniques, tools and strategies that enhance skills and meet the educational needs of students.